Problems and Constraints of Planning for Development in Libya - MENESI , AHMED; ABDUSSALAM, ALI (Dirasat in Economics and Business, 1981)
Libya, like other developing countries, has tried planning as a means of economic development. That is, it tried to pool its resources and channel them for development with the aim of improving the standard of living of the population. The first experience in development planning was the five-year plan 1963-1968. The total expenditure for this plan was LD. 290 million (about $ 812 million). The bulk of the expenditure (about 59%) went to developing the infrastructure. A second five year plan was prepared in 1969, but it was never implemented because a revolution took place at that time. That plan was re-evaluated and a three-year plan 1973-75 was carried out instead. The allocations for this plan amounted to LD. 1965 million (about $ 6563 million). A large portion of the development expenditure (about 42%) went to agriculture and industry. For the main objectives of the plan were to stimulate domestic production and achieve more equitable distribution of income among the population.